2013
DOI: 10.1038/ejhg.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

A novel in-frame deletion affecting the BAR domain of OPHN1 in a family with intellectual disability and hippocampal alterations

Abstract: Oligophrenin-1 (OPHN1) is one of at least seven genes located on chromosome X that take part in Rho GTPase-dependent signaling pathways involved in X-linked intellectual disability (XLID). Mutations in OPHN1 were primarily described as an exclusive cause of non-syndromic XLID, but the re-evaluation of the affected individuals using brain imaging displayed fronto-temporal atrophy and cerebellar hypoplasia as neuroanatomical marks. In this study, we describe clinical, genetic and neuroimaging data of a three gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…All three patients present with psychomotor delay, hypotonia, seizures, speech delay, and ataxic gait, which is consistent with previously reported cases (Al-Owain et al 2011;Bergmann et al 2003;Billuart et al 2000;Busa et al 2017;Chabrol et al 2005;des Portes et al 2004;Madrigal et al 2008;Moortgat et al 2018;Philip et al 2003;Santos-Reboucas et al 2014;Zanni et al 2005). Additionally, two of the three probands were diagnosed with strabismus, while the third was reported to have pseudostrabismus (Table 1).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…All three patients present with psychomotor delay, hypotonia, seizures, speech delay, and ataxic gait, which is consistent with previously reported cases (Al-Owain et al 2011;Bergmann et al 2003;Billuart et al 2000;Busa et al 2017;Chabrol et al 2005;des Portes et al 2004;Madrigal et al 2008;Moortgat et al 2018;Philip et al 2003;Santos-Reboucas et al 2014;Zanni et al 2005). Additionally, two of the three probands were diagnosed with strabismus, while the third was reported to have pseudostrabismus (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Review of the three patients' medical records revealed variability in their phenotypes in comparison to the common features reported in the literature (Table 1) (Al-Owain et al 2011;Bergmann et al 2003;Busa et al 2017;Chabrol et al 2005;des Portes et al 2004;Madrigal et al 2008;Moortgat et al 2018;Philip et al 2003;Santos-Reboucas et al 2014;Zanni et al 2005). This was particularly true for the dysmorphisms previously associated with OPHN1 variants, with Patients 2 and 3 lacking most of the previously reported common facial features (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The next challenges will be to decipher the mechanisms by which OPHN1 regulates fusion pore dynamics and to further explore the importance of the OPHN1 BAR domain in endocytic processes. Genetic mutations in OPHN1 gene leading either to the deletion of the BAR domain or to a non-functional BAR domain have recently been reported in patient with an intellectual disability [30,31] . Along this same line, it would be of primary interest to investigate whether, patients with mutations in the OPHN1 gene display neuroendocrine disorders in addition to neuronal defects and associated cognitive disabilities.…”
Section: Conclusion: Oligophrenin-1 Is a Molecular Switch Between Exomentioning
confidence: 99%